A climate-dependent spatial epidemiological model for the transmission risk of West Nile virus at local scale - Angelou, Anastasia; Kioutsioukis, Ioannis; Stilianakis, Nikolaos (One Health, 2021)
In this study, initial elements of a modelling framework aimed to become a spatial forecasting model for the transmission risk of West Nile virus (WNV) are presented. The model describes the dynamics of a WNV epidemic in population health states of mosquitoes, birds and humans and was applied to the case of Greece for the period 2010-2019. Calibration was performed with the available epidemiological data from the Hellenic Centre for Disease Control and Prevention and the environmental data from the European Union's earth observation program, Copernicus. Numerical results of the model for each municipality were evaluated against observations. Specifically, the occurrence of WNV, the number of infected humans and the week of incidence predicted from the model were compared to the corresponding numbers from observations. The results suggest that dynamic downscaling of a climate-dependent epidemiological model is feasible down-to roughly 80km(2). This below nomenclature of territorial units for statistics (NUTS) 3 level represents the municipalities being the lowest level of administrative units, able to cope with WNV and take actions. The average detection probability in hindcast mode was 72%, improving strongly as the number of infected humans increased. Using the developed model, we were also able to show the fundamental importance of the May temperatures in shaping the WNV dynamics. The modeling framework couples epidemiological and environmental dynamical variables with surveillance data producing risk maps downscaled at a local level. The approach can be expanded to provide targeted early warning probabilistic forecasts that can be used to inform public health policy decision making.
CRIS-Team WoS Importer:2021-10-29

A DISTRIBUTED OPTIMAL CONTROL MODEL APPLIED to COVID-19 PANDEMIC - Kovacevic, Raimund M.; Stilianakis, Nikolaos; Veliov, Vladimir M. (SIAM Journal on Control and Optimization, 2022)
In this paper, a distributed optimal control epidemiological model is presented. The model describes the dynamics of an epidemic with social distancing as a control policy. The model belongs to the class of continuous-time models, usually involving ordinary/partial differential equations, but has a novel feature. The core model-a single integral equation-does not explicitly use transition rates between compartments. Instead, it is based on statistical information on the disease status of infected individuals, depending on the time since infection. The approach is especially relevant for the coronavirus disease 2019 (COVID-19) in which infected individuals are infectious before onset of symptoms during a relatively long incubation period. Based on the analysis of the proposed optimal control problem, including necessary optimality conditions, this paper outlines some efficient numerical approaches. Numerical solutions show some interesting features of the optimal policy for social distancing, depending on the weights attributed to the number of isolated individuals with symptoms and to economic losses due to the enforcement of the control policy. The general nature of the model allows for inclusion of additional epidemic features with minor adaptations in the basic equations. Therefore, the modeling approach may contribute to the analysis of combined intervention strategies and to the guidance of public health decisions.
CRIS-Team Scopus Importer:2022-06-03
Keywords: epidemiology; integral equation; optimal control

An epidemiological model for mosquito host selection and temperature-dependent transmission of West Nile virus - Fasano, Augusto; Riccetti, Nicola; Angelou, Anastasia; Gomez-Ramirez, Jaime; Ferraccioli, Federico; Kioutsioukis, Ioannis; Stilianakis, Nikolaos (Scientific Reports, 2022)
We extend a previously developed epidemiological model for West Nile virus (WNV) infection in humans in Greece, employing laboratory-confirmed WNV cases and mosquito-specific characteristics of transmission, such as host selection and temperature-dependent transmission of the virus. Host selection was defined by bird host selection and human host selection, the latter accounting only for the fraction of humans that develop symptoms after the virus is acquired. To model the role of temperature on virus transmission, we considered five temperature intervals (≤ 19.25 °C; > 19.25 and < 21.75 °C; ≥ 21.75 and < 24.25 °C; ≥ 24.25 and < 26.75 °C; and > 26.75 °C). The capacity of the new model to fit human cases and the week of first case occurrence was compared with the original model and showed improved performance. The model was also used to infer further quantities of interest, such as the force of infection for different temperatures as well as mosquito and bird abundances. Our results indicate that the inclusion of mosquito-specific characteristics in epidemiological models of mosquito-borne diseases leads to improved modelling capacity.
CRIS-Team Scopus Importer:2022-12-02

A quartet method based on variable neighborhood search for biomedical literature extraction and clustering - Consoli, Sergio; Stilianakis, Nikolaos (International Transactions in Operational Research, 2017)
Medline/PubMed is the largest reference database collecting, organizing, and analyzing biomedical literature. We propose an automated methodology that is capable of searching relevant references for systematic reviews and meta-analysis from the Medline/PubMed database, and then to visualize the retrieved bibliography through an intuitive method based on a graph layout. In particular, document relationships are represented via the quartet method of hierarchical clustering. As this novel approach is based on an NP-hard combinatorial problem, a reduced variable neighborhood search is used for producing the graph of document clusters as output from the input distance matrix whereby the number of clusters is not known in advance. The distance matrix is derived from the link-ranking XML data returned by PubMed with the search results. It is demonstrated how the method allows to retrieve biomedical related bibliography, to find the structure of the literature collection examined, and to detect linked works within thematic areas of interest. With this methodology, scientists are assisted in the analysis of complex citations networks from the biomedical literature.
EVALuna2:34193

Assessment of West nile virus transmission risk from a weather-dependent epidemiological model and a global sensitivity analysis framework - Kioutsioukis, Ioannis; Stilianakis, Nikolaos (Acta Tropica, 2019)
West Nile virus (WNV) transmission risk is strongly related to weather conditions due to the sensitivity of the mosquitoes to climatic factors. We assess the WNV transmission risk of humans to seasonal weather conditions and the relative effects of parameters affecting the transmission dynamics. The assessment involves a known epidemiological model we extend to account for temperature and precipitation and a global uncertainty and sensitivity analysis framework. We focus on three relevant quantities, the basic reproduction number (R 0 ), the minimum infection rate (MIR), and the number of infected individuals. The highest-priority weather-related WNV transmission risks can be attributed to the birth and death rate of mosquitoes, the biting rate of mosquitoes to birds, and the probability of transmission from birds to mosquitoes. Global sensitivity analysis indicates that these parameters make up a big part of the explained variance in R 0 and MIR. The analysis allows for a dynamic assessment over time capturing the period parameters are more relevant than others. Global uncertainty and sensitivity analysis of WNV transmission risk to humans enable insights into the relative importance of individual parameters of the transmission cycle of the virus facilitating the understanding of the dynamics and the implementation of tailored control strategies.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Global sensitivity analysis; Infectious disease epidemiology; Mediterranean; Model; Prediction; Transmission risk; Weather; West Nile virus

Association of sociodemographic and environmental factors with the mental health status among preschool children-Results from a cross-sectional study in Bavaria, Germany - Zach, Angelika; Meyer, Nicole; Hendrowarsito, Lana; Kolb, Stefanie; Bolte, Gabriele; Nennstiel-Ratzel, Uta; Stilianakis, Nikolaos; Herr, Caroline (International Journal of Hygiene and Environmental Health, 2016)
It has been reported that a great proportion of mental health disorders have an origin in early childhood. In order to evaluate factors possibly associated with children's health, the health monitoring units have been established since 2004 in six study regions in Bavaria, Germany. The second health monitoring survey, implemented in 2005-06, focuses on the mental health status of preschool children. The goal of this study is (1) to examine the association of sociodemographic and environmental factors with mental health and (2) to analyze the applicability of the results of the health monitoring units to all preschool children in Bavaria by calculating weighting factors.Data on 6206 preschool children are available. Logistic regression analysis is applied to analyze possible associations with mental health. A weighting method is applied to correct for deviances compared to the whole population of preschool children in Bavaria (N=132,783).11% of preschool children show mental health problems. Regarding different indicators of sociodemographic status, low household income [unadjusted OR 3.34, 95% CI: 2.23-4.98] shows the strongest association of mental health problems. Non-accessibility of green space [unadjusted OR 2.74, 95% CI: 1.87-4.00] is also strongly associated with mental health. The results of the unweighted and weighted analysis are similar.Our findings suggest that sociodemographic status and factors in the living environment show associations with mental health of children. Based on the results of the unweighted and weighted analyses, the second health monitoring analysis shows little deviances compared to data of all Bavarian preschool children. Therefore, the results can be compared to all Bavarian preschool children.
EVALuna2:5552

Beware of regional heterogeneity when assessing the role of schools in the SARS-CoV-2 second wave in Italy - Assche, Simona Bignami-Van; Boujija, Yacine; Ghio, Daniela; Stilianakis, Nikolaos (The Lancet Regional Health - Europe, 2021)
CRIS-Team WoS Importer:2021-08-27
Keywords: second wave; disease incidence; COVID-19; regional heterogeneity; Italy; school opening; SARS-CoV-2

Droplets and aerosols: An artificial dichotomy in respiratory virus transmission - Drossinos, Yannis; Weber, Thomas P.; Stilianakis, Nikolaos (Health Science Reports, 2021)
In the medical literature, three mutually non-exclusive modes of pathogen transmission associated with respiratory droplets are usually identified: contact, droplet, and airborne (or aerosol) transmission. The demarcation between droplet and airborne transmission is often based on a cut-off droplet diameter, most commonly 5 mu m. We argue here that the infectivity of a droplet, and consequently the transmissivity of the virus, as a function of droplet size is a continuum, depending on numerous factors (gravitational settling rate, transport, and dispersion in a turbulent air jet, viral load and viral shedding, virus inactivation) that cannot be adequately characterized by a single droplet diameter. We propose instead that droplet and aerosol transmission should be replaced by a unique airborne transmission mode, to be distinguished from contact transmission.
CRIS-Team WoS Importer:2021-07-23

Fomites, hands, and the transmission of respiratory viruses - Weber, Thomas P.; Stilianakis, Nikolaos (Journal of Occupational and Environmental Hygiene, 2020)
CRIS-Team Scopus Importer:2020-12-25
Keywords: Contact; fomites; hands; skin; transmission mode; virus

Host selection and forage ratio in West Nile virus-transmitting Culex mosquitoes: Challenges and knowledge gaps - Riccetti, Nicola; Fasano, Augusto; Ferraccioli, Federico; Gomez-Ramirez, Jaime; Stilianakis, Nikolaos (Plos Neglected Tropical Diseases, 2022)
BACKGROUND: To date, no specific therapy or vaccination is available for West Nile virus (WNV) infections in humans; preventive strategies represent the only possibility to control transmission. To focus these strategies, detailed knowledge of the virus dynamics is of paramount importance. However, several aspects of WNV transmission are still unclear, especially regarding the role of potential vertebrate host species. Whereas mosquitoes' intrinsic characteristics cause them to favour certain hosts (host preference), absolute selection is impossible in natural settings. Conversely, the selection carried out among available hosts and influenced from hosts' availability and other ecological/environmental factors is defined as host selection. METHODOLOGY/PRINCIPAL FINDINGS: In July 2022, we searched PubMed database for original articles exploring host selection among WNV-transmitting Culex mosquitoes, the main WNV vector. We considered only original field studies estimating and reporting forage ratio. This index results from the ratio between the proportion of blood meals taken by mosquitoes on potential host species and the hosts' relative abundance. From the originally retrieved 585 articles, 9 matched the inclusion criteria and were included in this review. All but one of the included studies were conducted in the Americas, six in the United States, and one each in Mexico and Colombia. The remaining study was conducted in Italy. American Robin, Northern Cardinal, and House Finch were the most significantly preferred birds in the Americas, Common Blackbird in Italy. CONCLUSIONS/SIGNIFICANCE: Although ornithophilic, all observed WNV-transmitting mosquitoes presented opportunistic feeding behaviour. All the observed species showed potential to act as bridges for zoonotic diseases, feeding also on humans. All the observed mosquitoes presented host selection patterns and did not feed on hosts as expected by chance alone. The articles observe different species of mosquitoes in different environments. In addition, the way the relative host abundance was determined differed. Finally, this review is not systematic. Therefore, the translation of our results to different settings should be conducted cautiously.
CRIS-Team Scopus Importer:2022-11-11

Identification of Climatic Factors Affecting the Epidemiology of Human West Nile Virus Infections in Northern Greece - Stilianakis, Nikolaos; Syrris, Vasileios; Petroliagkis, Thomas; Part, Peeter; Gewehr, Sandra; Kalaitzopoulou, Stella; Mourelatos, Spiros; Baka, Agoritsa; Pervanidou, Danai; Vontas, John; Hadjichristodoulou, Christos (PLoS ONE, 2016)
Climate can affect the geographic and seasonal patterns of vector-borne disease incidence such as West Nile Virus (WNV) infections. We explore the association between climatic factors and the occurrence of West Nile fever (WNF) or West Nile neuro-invasive disease (WNND) in humans in Northern Greece over the years 2010-2014. Time series over a period of 30 years (1979-2008) of climatic data of air temperature, relative humidity, soil temperature, volumetric soil water content, wind speed, and precipitation representing average climate were obtained utilising the ECMWF's (European Centre for Medium-Range Weather Forecasts) Re-Analysis (ERA-Interim) system allowing for a homogeneous set of data in time and space. We analysed data of reported human cases of WNF/WNND and Culex mosquitoes in Northern Greece. Quantitative assessment resulted in identifying associations between the above climatic variables and reported human cases of WNF/WNND. A substantial fraction of the cases was linked to the upper percentiles of the distribution of air and soil temperature for the period 1979-2008 and the lower percentiles of relative humidity and soil water content. A statistically relevant relationship between the mean weekly value climatic anomalies of wind speed (negative association), relative humidity (negative association) and air temperature (positive association) over 30 years, and reported human cases of WNF/WNND during the period 2010-2014 could be shown. A negative association between the presence of WNV infected Culex mosquitoes and wind speed could be identified. The statistically significant associations could also be confirmed for the week the WNF/WNND human cases appear and when a time lag of up to three weeks was considered. Similar statistically significant associations were identified with the weekly anomalies of the maximum and minimum values of the above climatic factors. Utilising the ERA-Interim re-analysis methodology it could be shown that besides air temperature, climatic factors such as soil temperature, relative humidity, soil water content and wind speed may affect the epidemiology of WNV.
EVALuna2:5550

On the transmission dynamics of sars-cov-2 in a temperate climate - Kioutsioukis, Ioannis; Stilianakis, Nikolaos (International Journal of Environmental Research and Public Health, 2021)
An epidemiological model, which describes the transmission dynamics of SARS-CoV-2 under specific consideration of the incubation period including the population with subclinical infections and being infective is presented. The COVID-19 epidemic in Greece was explored through a Monte Carlo uncertainty analysis framework, and the optimal values for the parameters that determined the transmission dynamics could be obtained before, during, and after the interventions to control the epidemic. The dynamic change of the fraction of asymptomatic individuals was shown. The analysis of the modelling results at the intra-annual climatic scale allowed for in depth investigation of the transmission dynamics of SARS-CoV-2 and the significance and relative importance of the model parameters. Moreover, the analysis at this scale incorporated the exploration of the forecast horizon and its variability. Three discrete peaks were found in the transmission rates throughout the investigated period (15 February–15 December 2020). Two of them corresponded to the timing of the spring and autumn epidemic waves while the third one occurred in mid-summer, implying that relaxation of social distancing and increased mobility may have a strong effect on rekindling the epidemic dynamics offsetting positive effects from factors such as decreased household crowding and increased environmental ultraviolet radiation. In addition, the epidemiological state was found to constitute a significant indicator of the forecast reliability horizon, spanning from as low as few days to more than four weeks. Embedding the model in an ensemble framework may extend the predictability horizon. Therefore, it may contribute to the accuracy of health risk assessment and inform public health decision making of more efficient control measures.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Asymptomatic infections; COVID-19; Epidemiological model; Humidity; Predictability; SARS-CoV-2; Temperature; Transmission

Population Health and COVID-19 in Canada: a Demographic Comparative Perspective - Ghio, Daniela; Acosta, Enrique; Fisman, David; Noymer, Andrew; Stilianakis, Nikolaos I.; Bignami-Van Assche, Simona; Stilianakis, Nikolaos (Canadian Studies in Population, 2021)
CRIS-Team Scopus Importer:2021-10-01

Satellite Earth Observation Data in Epidemiological Modeling of Malaria, Dengue and West Nile Virus: A Scoping Review - Parselia, Elisavet; Kontoes, Charalampos; Tsouni, Alexia; Hadjichristodoulou, Christos; Kioutsioukis, Ioannis; Magiorkinis, Gkikas; Stilianakis, Nikolaos (Remote Sensing, 2019)
Earth Observation (EO) data can be leveraged to estimate environmental variables that influence the transmission cycle of the pathogens that lead to mosquito-borne diseases (MBDs). The aim of this scoping review is to examine the state-of-the-art and identify knowledge gaps on the latest methods that used satellite EO data in their epidemiological models focusing on malaria, dengue and West Nile Virus (WNV). In total, 43 scientific papers met the inclusion criteria and were considered in this review. Researchers have examined a wide variety of methodologies ranging from statistical to machine learning algorithms. A number of studies used models and EO data that seemed promising and claimed to be easily replicated in different geographic contexts, enabling the realization of systems on regional and national scales. The need has emerged to leverage furthermore new powerful modeling approaches, like artificial intelligence and ensemble modeling and explore new and enhanced EO sensors towards the analysis of big satellite data, in order to develop accurate epidemiological models and contribute to the reduction of the burden of MBDs.
CRIS-Team WoS Importer:2019-09-20

The Relevance of Leisure Noise to Hearing Threshold Shifts: A Longitudinal Analysis Among Adolescents - Walser-Reichenbach, Sandra M.; Gerstner, Doris G.; Twardella, Dorothee; Jenkac, Christina; Weilnhammer, Veronika; Hendrowarsito, Lana; Perez-Alvarez, Carmelo; Steffens, Thomas; Stilianakis, Nikolaos; Herr, Caroline E.W.; Heinze, Stefanie (Journal of Speech Language and Hearing Research, 2022)
PURPOSE: The aim of this study was to analyze the association of total leisure noise exposure and hearing threshold shifts over 5 years among adolescents enrolled in the Ohrkan cohort study. METHOD: The Ohrkan cohort of 2,148 students aged 13-19 years was recruited from 2009 to 2011 and followed up 5 years later. Complete baseline and follow-up reports on exposure and outcome were available for 989 participants. Leisure noise exposure was assessed by questionnaires, and clinical audiometric examinations were performed. Two outcomes were defined: occurrence of the Niskar notch pattern and audiometry showing maximum hearing threshold values at 3, 4, and 6 kHz (both ears). Longitudinal analysis using generalized estimating equations was performed. RESULTS: High total leisure noise exposure, defined as an energy equivalent of a 40-hr week of > 85 dBA, was estimated for 32.7% of students at baseline and 63.8% at follow-up. A noise notch was observed in 1.1% of adolescents at baseline and 3.3% at follow-up. At baseline, the maximum measured threshold shift was 55 dB, which increased to 85 dB at the follow-up. Longitudinal analysis did not reveal an association between leisure noise exposure and hearing thresholds. Hearing threshold shifts or noise notches were associated with sex, school type, and time point of measurement. CONCLUSIONS: No relationship was found between leisure noise and hearing thresholds. Male adolescents and those attending secondary general schools, with graduation following completion of ninth or 10th grade, had a greater likelihood of developing hearing threshold shifts. Prevention programs should focus on these risk groups. SUPPLEMENTAL MATERIAL: https://doi.org/10.23641/asha.19233462.
CRIS-Team Scopus Importer:2022-03-18

What aerosol physics tells us about airborne pathogen transmission - Drossinos, Yannis; Stilianakis, Nikolaos (Aerosol Science and Technology, 2020)
CRIS-Team WoS Importer:2020-04-28